Case Studies for Health, Research and Practice in Australia and New Zealand - Whiteing, Nicola; Shinners, Lucy; Graham, Nicole; Nasrawi, Dima; Wilson, Donna; Foster, Anna; Kunst, Elicia; Greenhill, Jennene (Open textbook library., 2023)
The OER includes case studies of 5 families from a variety of backgrounds in metropolitan and regional Queensland (QLD), New South Wales (NSW), and Victoria (VIC), Australia. Case studies have been popular in nursing to help students bring their learning to life and enhance their critical thinking. However, often case studies appear in one unit or one particular content area to aid students learning for a particular condition or point in time. Taking a transformational, place-based approach, the OER case studies for health are set within metropolitan and regional areas, so learning is contextual and relatable. Case studies increase in complexity so that students can be introduced to and ‘get to know’ the families from their first year of study. As students progress through their studies, they meet the families again in different, often more complex scenarios. The families experience a variety of political and socio-economic circumstances, which helps students to learn about various healthcare contexts, build knowledge and understanding about the families’ circumstances from a holistic, person-centred, interprofessional perspective, and engage at a deeper level.